1984
DOI: 10.1149/1.2115697
|View full text |Cite
|
Sign up to set email alerts
|

Kolbe Electrolysis of Mixtures of Aliphatic Organic Acids

Abstract: Kolbe electrolysis of mixtures of n‐butanoic with n‐hexanoic acid and propanoic with n‐hexanoic acid have been performed in aqueous solution at a smooth platinum anode. Typically, hexane production by the oxidation of butanoic acid, or butane production from propanoic acid, in aqueous solution is not observed to exceed a few percent. In the current work, significant increases of these products were observed. In addition, a substantial fraction of the remaining C3 or C4 acids reacted were converted to mixed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 47 publications
(60 citation statements)
references
References 4 publications
0
60
0
Order By: Relevance
“…Furthermore, increased temperature during Kolbe electrolysisw as reportedt oi ncrease yields of non-Kolbe products [29] and lower the CEs. Thef inding strongly emphasizes the need forac omprehensive and detailed monitoring and controlling of reactionp arameters when evaluating input parameters for Kolbe electrolysis and electroorganic reactions in general.…”
Section: Mechanistic Study On Kolbe Electrolysis In Aqueous Solutionsmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, increased temperature during Kolbe electrolysisw as reportedt oi ncrease yields of non-Kolbe products [29] and lower the CEs. Thef inding strongly emphasizes the need forac omprehensive and detailed monitoring and controlling of reactionp arameters when evaluating input parameters for Kolbe electrolysis and electroorganic reactions in general.…”
Section: Mechanistic Study On Kolbe Electrolysis In Aqueous Solutionsmentioning
confidence: 96%
“…[27,29,30,[46][47][48][49] Accordingly,a ni ncreased yield of Kolbe product demands ah igher electric poweri nput (P el )c ompared to non-Kolbe product formation, as the power consumption of an www.chemsuschem.org electrochemical cell is definedb yt he product of the current (i) and the cell voltage (E cell )a ss hown in Equation (1). [27,29,30,[46][47][48][49] Accordingly,a ni ncreased yield of Kolbe product demands ah igher electric poweri nput (P el )c ompared to non-Kolbe product formation, as the power consumption of an www.chemsuschem.org electrochemical cell is definedb yt he product of the current (i) and the cell voltage (E cell )a ss hown in Equation (1).…”
Section: Considerations On Supporting Electrolytes For Kolbe Electrolmentioning
confidence: 99%
“…[7] About 50 years later, it was revealed that the possible reaction pathways of the electrochemical oxidization of carboxylates also include alcohol formation resulting from intermediate carbocations being formed at the anode ( Figure S1). [7,[9][10][11][12][13][14][15][16][17][18] Note that the carboxylate, i. e. the carboxylic acid anion, is the starting compound of the electrochemical reaction [7] (see also Figure S1). [7,[9][10][11][12][13][14][15][16][17][18] Note that the carboxylate, i. e. the carboxylic acid anion, is the starting compound of the electrochemical reaction [7] (see also Figure S1).…”
Section: Introductionmentioning
confidence: 99%
“…[7,[9][10][11][12][13][14][15][16][17][18] Among others, it was reported that a high current density, a high educt concentration (e. g. 0.5 mol L À1 ) and a neutral or slightly acidic pH promote the Kolbe-reaction over the intermediate formation of carbocations and related follow-up reactions in aqueous media (see Fig-ure S1 for the details on the example of n-octanoic acid/noctanoate). [7,[9][10][11][12][13][14][15][16][17][18] Among others, it was reported that a high current density, a high educt concentration (e. g. 0.5 mol L À1 ) and a neutral or slightly acidic pH promote the Kolbe-reaction over the intermediate formation of carbocations and related follow-up reactions in aqueous media (see Fig-ure S1 for the details on the example of n-octanoic acid/noctanoate).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation